2022
DOI: 10.1039/d1py01691a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent homopolypeptide toroids

Abstract: Homopolypeptide poly(γ-benzyl-l-glutamate) can self-assemble into fluorescent toroids following an end-to-end closure mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Polypeptides are promising candidates for biomedical applications due to their close affiliation to proteins. Compared to other degradable polymers, polypeptides feature various secondary structures, including α-helices and β-sheets. This feature has a huge impact on their self-assembly behavior. , Poly-γ-benzyl- l -glutamate (PBLG) is a particularly interesting polypeptide that adopts the head-to-tail (HTT) arrangement in helicogenic solvents (such as dioxane, ethylene dichloride, and chloroform) because each α-helical PBLG molecule has a permanent dipole moment along the direction of its rod axis (Scheme S1A,B). With the introduction of a poor solvent, these HTT chains further aggregate under the side-by-side antiparallel (SSA) arrangement (Scheme S1C) and also due to the permanent dipole moments .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polypeptides are promising candidates for biomedical applications due to their close affiliation to proteins. Compared to other degradable polymers, polypeptides feature various secondary structures, including α-helices and β-sheets. This feature has a huge impact on their self-assembly behavior. , Poly-γ-benzyl- l -glutamate (PBLG) is a particularly interesting polypeptide that adopts the head-to-tail (HTT) arrangement in helicogenic solvents (such as dioxane, ethylene dichloride, and chloroform) because each α-helical PBLG molecule has a permanent dipole moment along the direction of its rod axis (Scheme S1A,B). With the introduction of a poor solvent, these HTT chains further aggregate under the side-by-side antiparallel (SSA) arrangement (Scheme S1C) and also due to the permanent dipole moments .…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the Self-Assembly Process of TPE-PBLG23 and TPE-PBLG46 with Different Water Contents. TPE-PBLG23 or TPE-PBLG 46 was dissolved in dioxane and self-assembled with the same solvent switching method described above.…”
mentioning
confidence: 99%
“…Intertwined fibers, cross-linked aggregates, and isolated nanotoroids were formed gradually with increasing water content (Figure l–o). It has been reported that the HTT chain formed by PBLG in THF can be more flexible than that in DOA, , which could lead to such different self-assembly behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…4,8−10 Recently, Du and coworkers discovered that selective solvents can impose a huge impact on the morphology of the homopolypeptide-based selfassembly from the nanotoroid to the nanorod. 11,12 Through the co-assembly of polypeptide mixtures, Lin and co-workers constructed superhelices with adjustable chirality regulated by the chiral homopolypeptides and copolypeptides. 13,14 Given the chiral structure of most polypeptides, it is of great significance to endow unique optical properties beyond their novel assembly structures, which can endow the biodegradable nanomaterials with certain photophysical activities to enable them to be applied in environmentally friendly optoelectronic devices and in biomedical fields.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation